2018
DOI: 10.1002/cam4.1677
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 regulates HDAC4‐mediated proliferation and apoptosis via decoying of miR‐140‐5p in osteosarcoma cells

Abstract: Noncoding RNAs regulate the initiation and progression of osteosarcoma (OS). The role of long noncoding RNA metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) playing in OS and whether the function it working out was achieved through HDAC4 pathway remain uncovered. In this study, we illustrated that MALAT1 was upregulated and was correlated with poor prognosis in OS patients. Meanwhile, we demonstrated that a depression of MALAT1 suppressed proliferation and promoted apoptosis in OS cell line HOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Especially for MALAT1, it was reported that MALAT1, as an important lncRNA in cancer, has been shown to promote the metastasis, proliferation, and invasion through various mechanisms (X. Zhang, Hamblin, & Yin, ). For example, MALAT1 could regulate the proliferation and apoptosis of osteosarcoma cells via decoying miR‐140‐5p (Sun & Qin, ). MALAT1 has been shown to promote the migration and invasion of lung cancer cells through targeting miR‐206 and Akt/mechanistic target of rapamycin (mTOR) signaling (Tang, Xiao, Chen, & Deng, ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially for MALAT1, it was reported that MALAT1, as an important lncRNA in cancer, has been shown to promote the metastasis, proliferation, and invasion through various mechanisms (X. Zhang, Hamblin, & Yin, ). For example, MALAT1 could regulate the proliferation and apoptosis of osteosarcoma cells via decoying miR‐140‐5p (Sun & Qin, ). MALAT1 has been shown to promote the migration and invasion of lung cancer cells through targeting miR‐206 and Akt/mechanistic target of rapamycin (mTOR) signaling (Tang, Xiao, Chen, & Deng, ).…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) lncRNA affects the apoptotic osteosarcoma cell machinery through the RhoA/ROCK signal transduction pathway [88]. MALAT1also regulates osteosarcoma cell proliferation and apoptosis through upregulation of histone deacetylase 4 (HDAC4) by decoying miR-140-5p [199].…”
Section: Lncrnas and Cell Death In Osteosarcomamentioning
confidence: 99%
“…The double DIG-labeled LNA microRNA probe (QIAGEN, Shanghai, China) for miR-140-5p was incubated with the paraffin-embedded osteosarcoma tissue sections. Briefly, after being deparaffinized, the tissue sections were treated with proteinase K (Roche, Basel, Switzerland), hybridized with 300 ng/mL probe at 60℃ for 16 h, then incubated with anti-digoxygenin-AP (AP-conjugated Fab fragments) (11093274910, Roche, Basel, Switzerland) at 25℃ for1 h, and lastly added with BM Purple (11442074001, Roche, Basel, Switzerland) for color reaction [16][17][18]. Osteosarcoma cells were plated into a 6-well plate with 3 × 10 5 cells in each well.…”
Section: Rna In Situ Hybridizationmentioning
confidence: 99%